CONTENT BASED INSTRUCTION IN TEACHING TOURISM AND ECONOMICS COURSES - Juraev, Abror; Sobirov, Tolib (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Recent years in higher education system of Uzbekistan witnessed deep reforms related with increasing the quality of education, better employment of graduates, improvement of foreign languages competences and strengthening the links in the knowledge triangle. When some universities started offering specialization courses in English or other languages, problem of matching objectives of the courses with the aim of improving English language competence came to agenda. The article depicts the situation at newly created Faculty of Tourism at Bukhara State University and the use of Content-Based Instruction in finding the solution. The new faculty consists of BA and MA degrees in fields related with Tourism, Hospitality, Economics, Fine Arts etc.